A retrospective epidemiological study of outpatient burn care during 2010-2019 in Iran - Hamidreza Hosseinpour; Hooman Kamran; Farzaneh Zahmatkesh Meimandi; Mohammad Amin Shahrbaf; Ramin Shekouhi; Maryam Salimi; Mohammad Reza Marzban; Maryam Sohooli; Mohammad Ali Hoghoughi (Elsevier, 2022)
Burn injury is considered the sixth most common cause of preventable death in the United States and is associated with major morbidity and mortality, especially in developing countries. Here, we aim to discuss the catastrophic effects of burn injury regarding its high prevalence. This retrospective cross-sectional study was conducted on patients referred to the outpatient clinics of two burns and plastic surgery referral centers from 2010 to 2019. Thirty-eight thousand and seven hundred thirty-four patients (n = 38,734) with a mean age of 27.5 ± 19.9 (Range: 1-99) were included in the study. Male patients (56.5%) were more than females (43.5%). Upper (30.0%) and lower (28.7%) limbs were the most common sites of injuries, while scald (49.8%) was the main etiology. Besides, patients' homes (74.8%) were the most common location of burn injuries. The mean body surface area injured was also 2.4 ± 1.8 %. The anatomical locations of burn injuries were statistically associated with age, sex, place, and etiology of injuries (all with P value < 0.001). In addition, the trendline of burn injuries during those nine years showed an overall decreasing trend in those years. In our study, the overall incidence of burn injuries in Fars Province was 63.6/100,000 person-years. The calculation of the incidence number of the outpatient burn was reported only in a few studies in the literature. In addition, the difference in the number of studied centers and patient selection in different areas makes it impossible to compare our study's incidence to other regions. We encourage physicians to obtain a standardized prevention program directed at various aspects of these injuries to reduce the functional and cosmetic impairments of this public health burden.